Mythology - Hamilton, Edith 1867-1963 (Little, 1942)
A collection of Greek and Roman myths from various classical sources arranged in section on the gods and early heroes, love and adventure stories, heroes before and during the Trojan War, and lesser myths. Includes a brief section on Norse mythology.